2009
DOI: 10.1007/s11695-009-9932-5
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Failed Vertical Banded Gastroplasty to Biliopancreatic Diversion, a Wise Option

Abstract: Our early results indicate that conversion of failed VBG to BPD is highly effective with acceptable morbidity. Our data show that the effect on weight is strongly dependent on the indication for the conversion. Conversion to BPD, in such a group of patients, is a wise alternative, since it may reduce operative risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…20 There are very few reports on use of BPD and BPD + DS as a conversion procedure after failed VBG. 10 patients, and found that it is very efficient. 21 They reported on 8 % leak rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 There are very few reports on use of BPD and BPD + DS as a conversion procedure after failed VBG. 10 patients, and found that it is very efficient. 21 They reported on 8 % leak rate.…”
Section: Discussionmentioning
confidence: 99%
“…Weiner et al 10 reported early results indicating that open conversion of failed VBG to BPD is a wise option and highly effective with acceptable morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After failed LAGB, different surgical options are possible, among them conversion to RYGB and SG have been historically taken into account in our clinical practice, both for satisfactory weight control and low-morbidity profile. Also malabsorptive interventions (bilio-pancreatic diversion with or without duodenal switch) were offered following failure of LAGB by some authors [10,[26][27][28], but up to now, these procedures have never been our choice, due to the relevant risks of malnutrition and vitamin/mineral deficiency. This article adds a contribution to the current literature about revisional bariatric surgery following LAGB failure, but larger series and longer followups are still needed to draw definitive conclusions.…”
Section: Open Access Journal Of Surgerymentioning
confidence: 99%
“…This potential problem has been traditionally dealt with by revisional surgery, which is known to carry significantly more risk than primary bariatric surgery. 3,4 Even when these technically challenging cases are performed well, there are clearly increased risks to revisional bariatric surgery versus primary bariatric surgery.…”
mentioning
confidence: 99%